Fluorescence-guided surgery in colorectal cancer; A review on clinical results and future perspectives. Issue 4 (April 2022) - Galema, Hidde A.; Meijer, Ruben P.J.; Lauwerends, Lorraine J.; Verhoef, Cornelis; Burggraaf, Jacobus; Vahrmeijer, Alexander L.; Hutteman, Merlijn; Keereweer, Stijn; Hilling, Denise E.
Abstract: Background: Colorectal cancer is the fourth most diagnosed malignancy worldwide and surgery is one of the cornerstones of the treatment strategy. Near-infrared (NIR) fluorescence imaging is a new and upcoming technique, which uses an NIR fluorescent agent combined with a specialised camera that can detect light in the NIR range. It aims for more precise surgery with improved oncological outcomes and a reduction in complications by improving discrimination between different structures. Methods: A systematic search was conducted in the Embase, Medline and Cochrane databases with search terms corresponding to 'fluorescence-guided surgery', 'colorectal surgery', and 'colorectal cancer' to identify all relevant trials. Results: The following clinical applications of fluorescence guided surgery for colorectal cancer were identified and discussed: (1) tumour imaging, (2) sentinel lymph node imaging, (3) imaging of distant metastases, (4) imaging of vital structures, (5) imaging of perfusion. Both experimental and FDA/EMA approved fluorescent agents are debated. Furthermore, promising future modalities are discussed. Conclusion: Fluorescence-guided surgery for colorectal cancer is a rapidly evolving field. The first studies show additional value of this technique regarding change in surgical management. Future trials should focus on patient related outcomes such as complication rates, disease free survival, and overall survival.